Revisiting the Compatibility of Islam and Democracy: A Reevaluation of the Concept of Shūrā - Hilal, Amjad; Ur-Rahman, Sami; Tahseen, Areeba (Al-Amīr Research Journal for Islamic Studies, 2023)
The discourse surrounding the compatibility of Islam and democracy has been subject to rigorous analysis and debate, often centering on the Islamic principle of shura and its correlation with democratic ideals. This research paper conducts a critical evaluation of these arguments to elucidate the intricate relationship between Islam and democracy. Contrary to assertions positing the inherent incompatibility of Islam and democracy, this study reveals that the notion of Shura’s inconsistency with democratic principles is unfounded. This misconception stems from a superficial interpretation of these concepts, neglecting their nuanced semantics and historical backgrounds. Through a comprehensive analysis of shura and democracy, alongside their evolutionary trajectories, it becomes evident that they share fundamental compatibilities. Both frameworks prioritize consultation and deliberation, empowering the populace in the decision-making process. Nonetheless, a notable distinction arises concerning the principle of secularism. While both shura and democracy champion civil liberties and popular empowerment, a fundamental contrast emerges regarding the basis of governance. In Islam, sovereignty is exclusively attributed to Allah, whereas in Western democracy, ultimate authority rests with the people. In conclusion, this reevaluation underscores the inherent compatibility between Islam and democracy, emphasizing the convergence of their foundational tenets. By recognizing the subtleties and historical contexts embedded within these concepts, a deeper understanding emerges, facilitating constructive discourse and collaboration between Islamic and democratic societies. Keywords: Islam, Democracy, Shura, Governance, Sovereignty, Consultation